Preliminary Hybrid Modeling of the Panama Canal: Operations and Salinity Diffusion - Luis Rabelo; Mario Marin; Petros Xanthopoulos; Carlos Arellano Lennox; Pedro Coiduras; Bernardo Campos; Luz Andrade; Ricardo Collins; Erwin Atencio; Daryelis Pitty (Modelling and Simulation in Engineering)
This paper deals with the initial modeling of water salinity and its diffusion into the lakes during lock operation on the Panama Canal. A hybrid operational model was implemented using the AnyLogic software simulation environment. This was accomplished by generating an operational discrete-event simulation model and a continuous simulation model based on differential equations, which modeled the salinity diffusion in the lakes. This paper presents that unique application and includes the effective integration of lock operations and its impact on the environment.